Tph Cells Expanded in Primary Sjögren’s Syndrome - Chen, Weiqian; Yang, Fan; Lin, Jin (Frontiers in Medicine, 2022)
Objectives PD-1+CXCR5–CD4+T peripheral helper cells, named Tph cells, contribute to B-cell immune responses and the production of antibodies in systemic lupus erythematosus and rheumatoid arthritis. However, the role of Tph cells was unknown in the pathogenesis of primary Sjögren’s syndrome (pSS). Here, we aim to explore the contribution of Tph cells in the development of pSS. Methods Sixty patients with pSS and 61 age and sex-matched healthy individuals were recruited for this study. The frequency of Tph cells in the blood was measured by flow cytometry. The expression of inducible T-cell costimulator (ICOS), MHC-II, IL-21, CCR2, CCR5, and CCR9 was evaluated in Tph cells. The relationship between Tph cells and indicators of clinical disease was assessed. Co-expression levels of PD-1, CXCR5, CD4, CCR2, and CCR5 in the salivary gland specimens from patients with pSS and patients with dry mouth and eyes but normal pathology were also analyzed. Results We demonstrated increased circulating Tph cells (7.53 ± 6.65% vs. 3.08 ± 1.31%, p < 0.0001) in patients with pSS (n = 60) compared to healthy controls (n = 61). Tph cells were significantly associated with the ESSDAI disease activity scores, IgG, ESR, IL-21, anti-SSA antibody, and CD138+/CD19+ plasma cells. Furthermore, ICOS was highly expressed in Tfh and Tph cells in patients with pSS. IL-21, MHC-II, CCR2, and CCR5 expression was higher in pSS Tph cells, and CCR9 expression was lower in pSS Tph cells than in pSS Tfh cells. Moreover, Tph cells and CCR2+CD4+T and CCR5+CD4+T cells were found in the labial gland of patients with pSS. Conclusion Our data show that Tph cells were enriched in peripheral blood and labial gland of patients with pSS. Circulating Tph cells correlated with disease activity scores, suggesting a crucial role of Tph in the development of pSS.